IT/IS strategy research and digitalization: An extensive literature review - Alexander Teubner; Jan Stockhinger (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2020)
IT/IS strategy is of central importance to practice and many well-developed lines of research have contributed to our understanding of IT/IS strategy. However, throughout the last decade, digitalization has fundamentally transformed the business world and put into question traditional strategy wisdom. As information technologies are the driver of this digital transformation, we can expect an even more fundamental change in IT/IS strategy thinking. To verify this expectation, we undertook an in-depth, extensive review of the academic literature on this topic. Our review, which is time-framed to the years 2008-2018, distils five different directions in the development of IT/IS strategy research. It also identifies a shift in how IT/IS strategy is defined and investigated over this period. Moreover, we present an emerging debate on how digitalization challenges traditional IT/IS strategy wisdom. As this debate is still in its infancy, we take it further by entering into the larger discussion on digitalization, including digital innovation, digital ecosystems, and digital transformation. Building on this, we derive at deeper insights on how IT/IS strategy could, should, or should better not be understood in the digital age.
Keywords: 650; IT/IS Strategy; IS Strategy; Digitalization; Digital Transformation; Digital Business Strategy; Digital Strategy